2012
DOI: 10.1242/dev.080135
|View full text |Cite
|
Sign up to set email alerts
|

Signalling from hindbrain boundaries regulates neuronal clustering that patterns neurogenesis

Abstract: SUMMARYDuring central nervous system development, neural progenitors are patterned to form discrete neurogenic and non-neurogenic zones. In the zebrafish hindbrain, neurogenesis is organised by Fgf20a emanating from neurons located at each segment centre that inhibits neuronal differentiation in adjacent progenitors. Here, we have identified a molecular mechanism that clusters fgf20a-expressing neurons in segment centres and uncovered a requirement for this positioning in the regulation of neurogenesis. Disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…Furthermore, EGFP expression in rhombomere neurons at the prim-15 stage (Fig. S4C) is also consistent with the previously reported pattern of fgf20a expression (Terriente et al, 2012). Taken together, these data supported the notion that fgf20a expression during fin regeneration is recapitulated by the enhancer trap zebrafish line, and that Fgf20a is an Fgf ligand that is locally expressed in the basal layer of the wound epidermis.…”
Section: The Fgf Ligands That Are Expressed During Fin Regenerationsupporting
confidence: 91%
“…Furthermore, EGFP expression in rhombomere neurons at the prim-15 stage (Fig. S4C) is also consistent with the previously reported pattern of fgf20a expression (Terriente et al, 2012). Taken together, these data supported the notion that fgf20a expression during fin regeneration is recapitulated by the enhancer trap zebrafish line, and that Fgf20a is an Fgf ligand that is locally expressed in the basal layer of the wound epidermis.…”
Section: The Fgf Ligands That Are Expressed During Fin Regenerationsupporting
confidence: 91%
“…Sema3fb and sema3gb are also expressed at the hindbrain rhombomere boundaries. When Terriente and colleagues knocked down sema3fb and sema3gb or nrp2a using morpholinos, they found reduced clustering of fgf20a‐ expressing neurons in the rhombomeres (Terriente, Gerety, Watanabe‐Asaka, Gonzalez‐Quevedo, & Wilkinson, ). The authors propose a model in which fgf20a ‐expressing neurons also express the nrp2a receptor and are restricted from migrating away from the center of the rhombomere by repulsive sema3fb and sema3gb at the rhombomere boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…In chick, it has been demonstrated that border cells include a population of Sox2‐expressing neural progenitor cells that give rise to neurons of both adjacent rhombomeres (Peretz et al, ). In zebrafish, these boundary cells express the chemorepellants Sema3fb and Sema3gb, which are critical for maintaining the positioning of Nrp2a‐expressing neuronal populations within the rhombomere (Terriente, Gerety, Watanabe‐Asaka, Gonzalez‐Quevedo, & Wilkinson, ). Boundary cells may help to determine cell affinity properties that drive the proper segregation of more differentiated rhombomere cells.…”
Section: Rhombomere Organization and Mechanisms Of Segregationmentioning
confidence: 99%